Estruturação do Sistema de desenvolvimento de startups em uma aceleradora por intermédio de gestão de portfólio - Vinícius Bortolussi Roman (2017)
The startup acceleration phenomenon is a recent trend in the field of entrepreneurship and offers a fertile field for researchers who deal with the problem of creating startups and their impacts. Although some foreign accelerators have already developed some billionaire companies, most of them still need to prove themselves as viable businesses and this will only be possible with the successes of the accelerated companies, since the business model of the accelerators is based, primarily, around the selling of startups. The challenges faced by the accelerators range from the selection of startups to the development of these companies and offering them to potential investors. Additionally, most accelerators do not have sufficient capital to maintain the operation until they perform the exit from the first few startups, so they are forced to seek alternative sources of revenue or close down their activities early. In this scenario, the objective of this dissertation is to create and deploy a Startups Development System (SDS) in an accelerator based on the startup development and portfolio management methods. Through the strategy of action research, and with the support of the board of the accelerator under study, the researcher made an intervention in the process of developing startups (PDS) by dividing it into phases with gates for decision making, according to the degree of maturity of the companies. In addition, portfolio management methods were applied to support managers in the selection and prioritization of startups, balancing and maximizing portfolio value. The information obtained was essential to adjust the acceleration process adopted by the company and to structure the portfolio seeking a balance and better management among the different categories of startups identified. The application of the methods allowed systematizing the SDS, generating knowledge for the accelerator and similar organizations as incubators and investment funds.